IMPROVING STUDENTS' LANGUAGE SKILLS IN BUSINESS ENGLISH COURSE: EXPERIMENTAL STUDY - Zuzana Hrdličková (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
It is evident from the PISA 2018 results that a trend in mean performance in reading has been declining in the Slovak Republic. The KEGA Project "Idioms in Business Communication", run at the Department of English Language, aims at improving reading literacy, widening formal and informal vocabulary and facilitating business communication. Both traditional and modern styles of language teaching are used. The control group of students does a traditional course and the experimental group of students enrols in a "Business Communication" e-course on LMS Moodle platform, as well. With the use of the Internet and supporting materials, this group is involved in various activities. The paper compares the study results of 144 first-year and 97 second-year students of the University of Economics in Bratislava achieved in departmental standardised business English tests after completing three courses in business English for advanced students. The method of Hypothesis Testing (t-Test) assesses the significance of the difference between the levels of knowledge of both groups. The research findings prove that the experimental group of students achieved better results in final evaluation than the control group of students. The results also confirm that an alternative form of business English teaching was effective.